EVALUATION OF HEMATOLOGICAL PARAMETERS AND THEIR ASSOCIATION WITH THYROID HORMONE LEVELS IN WOMEN OF REPRODUCTIVE AGE: A COMPARATIVE STUDY - Trivedi, Pawan; Rai, Priyanka (Student’s Journal of Health Research Africa, 2024)
Background Thyroid hormones, particularly triiodothyronine (T3) and thyroxine (T4), are important for the regulation of metabolism and organ function, with imbalances linked to health issues such as hypothyroidism and hyperthyroidism. This investigation seeks to offer meaningful information on the clinical handling of hematological abnormalities linked to thyroid disorders, thereby contributing to improved health outcomes for those affected. Methods A one-year study was conducted at Maharshi Devraha Baba Autonomous State Medical College, including 500 non-pregnant female patients diagnosed with thyroid disorders. Participants were classified into hyperthyroid and hypothyroid groups based on clinical symptoms and laboratory results, with a control cohort of 100 age-matched females having normal thyroid function. Blood samples were analyzed for serum T3, T4, and TSH levels, along with hematological parameters, using a hematology analyzer. Results The study included 500 non-pregnant females, with 250 diagnosed with hypothyroidism, 250 with hyperthyroidism, and 100 euthyroid controls. Hypothyroid patients had significantly lower T3 (1.2 ± 0.35 nmol/L), T4 (54.40 ± 37.60 nmol/L), and elevated TSH (145.67 ± 192.40 mIU/L). Hematological analyses revealed lower hemoglobin (11.30 ± 1.10 g/dL) and RBC counts (4.02 ± 0.45 x10^6/µL) in hypothyroid subjects compared to euthyroid counterparts. No prominent variations were found in hematological parameters between hyperthyroid and euthyroid groups, although hypothyroid patients showed higher RDW and AEC. Conclusion The investigation demonstrates a significant correlation between thyroid dysfunction and hematological abnormalities, especially anemia in hypothyroid patients, emphasizing the need to evaluate thyroid hormone levels in women with unexplained anemia for better management. Recommendation Ongoing studies and collaborative endeavors are needed to enhance the understanding of hypothyroidism, ultimately improving patient treatment both within and outside of the community.